2017
DOI: 10.1002/eco.1861
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydropeaking on downstream fish habitat at the Goesan Dam in Korea

Abstract: The impact of hydropeaking on downstream fish habitat was investigated. The study area is a 2.3‐km long reach of the Dal River, located downstream from the Goesan Dam, Korea. Such short‐term effects of hydropeaking as flow unsteadiness, down‐ramping rate, transport of benthic macro‐invertebrate, and changes in composite suitability index (CSI) and weighted usable area (WUA) were examined. To assess the change in CSI and WUA, physical habitat simulations were carried out. The 2D unsteady flow model and the habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This indicates that the water release from the dam significantly affects the habitat suitability of the target species. This is consistent with previous findings [16][17][18]46,47].…”
Section: Natural Flow Regime Versus Dam Dischargesupporting
confidence: 94%
See 3 more Smart Citations
“…This indicates that the water release from the dam significantly affects the habitat suitability of the target species. This is consistent with previous findings [16][17][18]46,47].…”
Section: Natural Flow Regime Versus Dam Dischargesupporting
confidence: 94%
“…That is, the magnitude of discharge is flattened over the year, and the downstream reach no longer experiences flood events. Changes in the natural flow regime due to hydropeaking may affect the aquatic habitat in the downstream reach from the dam [17,18,[50][51][52][53][54]. However, the upstream dam often releases large amounts of water during the flood season.…”
Section: Restoration Of Flushing Flood Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical habitat simulation is a numerical tool that quantifies the habitats for target species in terms of the physical habitat variables in a stream. Previous studies showed that released water from a dam adversely affects the downstream fish habitat [45][46][47][48]. A variety of physical habitat simulations have been carried out, showing that hydropeaking and thermopeaking flows decrease habitat suitability for target species in the downstream reach of the dam [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%